Evaluation of environmental factors and microbial community structure in an important drinking-water reservoir across seasons - Feng, Jie; Zhou, Letian; Zhao, Xiaochao; Chen, Jianyi; Li, Zhi; Liu, Yongfeng; Ou, Lei; Xie, Zixin; Wang, Miao; Yin, Xue; Zhang, Xin; Li, Yan; et al. (Frontiers in Microbiology, 2023)
The composition of microbial communities varies in water and sediments, and changes in environmental factors have major effects on microbiomes. Here, we characterized variations in microbial communities and physicochemical factors at two sites in a large subtropical drinking water reservoir in southern China. The microbiomes of all sites, including the diversity and abundance of microbial species, were determined via metagenomics, and the relationships between microbiomes and physicochemical factors were determined via redundancy analysis. The dominant species in sediment and water samples differed; Dinobryon sp. LO226KS and Dinobryon divergens were dominant in sediment samples, whereas Candidatus Fonsibacter ubiquis and Microcystis elabens were dominant in water. The diversity was also significantly different in microbial alpha diversity between water and sediment habitats (p < 0.01). The trophic level index (TLI) was the major factor affecting the microbial community in water samples; Mycolicibacterium litorale and Mycolicibacterium phlei were significantly positively related to TLI. Furthermore, we also studied the distribution of algal toxin-encoding genes and antibiotic-resistant genes (ARGs) in the reservoir. It found that water samples contained more phycotoxin genes, with the cylindrospermopsin gene cluster most abundant. We found three genera highly related to cylindrospermopsin and explored a new cyanobacteria Aphanocapsa montana that may produce cylindrospermopsin based on the correlation through network analysis. The multidrug resistance gene was the most abundant ARG, while the relationship between ARGs and bacteria in sediment samples was more complicated than in water. The results of this study enhance our understanding of the effects of environmental factors on microbiomes. In conclusion, research on the properties, including profiles of algal toxin-encoding genes and ARGs, and microbial communities can aid water quality monitoring and conservation.